PENGENALAN INFRASTRUKTUR TEKNOLOGI INFORMASI PADA APLIKASI REKAM MEDIS ELEKTRONIK - Rohmadi, Rohmadi; Harjanti, Harjanti; Widiantoro, Reza; Sinatria Deto Wijanarko, Caliulinius (APTIRMIKI, 2025)
The knowledge of Vocational High School (SMK) students regarding Electronic Health Records (EHR), which is part of the Information Technology (IT) system, is vital in the healthcare sector. SMK graduates are expected to possess sufficient knowledge to support the implementation of this technology in the workplace, particularly in hospitals or other healthcare facilities. The problem experienced by the students is the lack of adequate material concerning information technology, specifically in the health sector. The current curriculum is focused on the general fundamentals of information technology. The activity aimed to introduce students to the IT infrastructure used in electronic health record systems, including hardware, software, and data security aspects. The method used for the activity was Health Education. The activity was held on March 19, 2025, and was attended by 101 participants. The event was interactive with discussions covering data leak prevention, how to create a public Internet Protocol (IP), and tracing servers on a domain. Participants were asked to write a material summary at the end of the activity to measure their understanding. This activity successfully increased the SMK students' understanding of IT infrastructure in EHR and is expected to strengthen graduates' readiness to meet industry needs, particularly in the health sector, as well as enhance their vigilance against cyber threats and human errors.